Innovative Work Behavior and Its Impact on Teacher Performance: The Role of Organizational Culture and Self Efficacy as Predictors - Sofiyan, Sofiyan; Sembiring, Rasmulia; Danilwan, Yuris; Anggriani, Rini; Sudirman, Acai (Journal of Education Reseach and Evaluation, 2022)
The dynamics of significant and sudden changes from the current pandemic have made many educational institutions experience challenges in fully adopting technology into the teaching and learning process. This condition makes every educator required to do work so that it is oriented to innovative work behavior. The consequences of an innovative work culture will encourage increased teacher performance during the current pandemic. This study aims to determine how big organizational culture and self-efficacy contribute to innovative work behavior and its impact on teacher performance. The research design uses a causal quantitative approach. For the acquisition of research data using an online questionnaire distribution instrument. The sample used in the study was 215 respondents. The basis for determining the sample is oriented to the non-probability sampling approach by using the purposive sampling formula. A structural equation modeling (SEM) approach using partial least squares (PLS) is used to test organizational culture and self-efficacy on innovative work behavior and its impact on teacher performance. Following the results of research data analysis, it shows that organizational culture has a positive and significant effect on innovative work behavior. Then it is concluded that self-efficacy has a positive and significant effect on innovative work behavior. For the results of data analysis, further research proves that innovative work behavior has a positive and significant effect on teacher performance.